The impact of work investment on performance - Cătălina Radu; Alecxandrina Deaconu; Sorina Ioana Mișu; Monica Triculescu (Amfiteatru Economic Journal, 2020)
The paper's main objective is to analyse the impact of work investment on performance. The research involved administering an online questionnaire, which collected information on work effort, perceived performance, burnout and job satisfaction. The study was conducted on a group of 313 participants, all active on the labour market - employees (with or without management position) and entrepreneurs in various fields of activity. Sampling was unlikely, based on the availability criterion. The results obtained claim that the perception of performance mediates the relationship between effort at work and satisfaction obtained through work itself, and burnout is moderate both in the relationship between effort and perception of performance, and in that between perception of performance and satisfaction through the work itself. Consistent with the literature and within the limits of the methodology used, it has been found that management functions are associated with a lower level of burnout than others, a greater power in decision-making means an increased ability to detach from problems, even if the investment in labour is appreciable.
Keywords: M12; M54; D91; 330; investment in work; effort; performance; job satisfaction; burnout